Study of Axiology in Scientific Field and Works - Karshiyev Shokhruh (Indonesian Journal of Cultural and Community Development, 2023)
The article is devoted to prevalence of axiological approaches in all areas of research. At first, axiology was a subject of philosophical study and evaluation. Our research indicates that it later studied in a variety of different disciplines, including physics, chemistry, sociology, linguistics, and literature. Additionally, it is crucial to carefully address topics like linguoaxiological methodologies, synchronic and diachronic features of axiology, and their adherence to the national culture and values when analyzing translations of hagiographic literature. The axiological approach to the study of hagiographic literature in translation studies degree of alternativeness in the context in the target language of the words of national culture, religion, Islamic morality etc.